The Defence of India - Vincent, Arthur (London Oxford University Press, 1922)
This book was digitized and reprinted from the collections of the University of California Libraries. It was produced from digital images created through the libraries$1 (Bmass digitization efforts. The digital images were cleaned and prepared for printing through automated processes. Despite the cleaning process, occasional flaws may still be present that were part of the original work itself, or introduced during digitization. This book and hundreds of thousands of others can be found online in the HathiTrust Digital Library at www.hathitrust.org.s
Keywords: Military Readiness -- India